PENGARUH SERVANT LEADERSHIP, HUMAN CAPITAL MANAGEMENT, DAN PENGEMBANGAN SDM TERHADAP KINERJA ANGGOTA DI POLRES LEBONG - Rahayu, Rani; Hidayati, Arifah; Waliamin, Janusi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to evaluate the influence of servant leadership, human capital management, and human resource development on the performance of members at the Lebong Police Department. The research employed a quantitative method with a population of 206 members, while the sample size was determined using the Slovin formula, resulting in 108 respondents. Data were collected through questionnaires, with primary data serving as the main source. The data were analyzed using multiple linear regression, including regression coefficient test, t-test, and F-test. The results showed that the coefficient of determination (R Square) was 81.4%, indicating that variations in members’ performance can be explained by servant leadership, human capital management, and human resource development. The F-test revealed that the regression model was significant simultaneously. The t-test results indicated that servant leadership had a negative and significant effect on performance, while HCM and human resource development had a positive and significant effect on members’ performance. The conclusion of this study is that human capital management and human resource development are the key factors in improving members’ performance, whereas servant leadership exerts a negative effect on the performance of members at the Lebong Police Department